Life psychosocial stresses and coronary artery disease - Babak Bagheri; Fatemeh Meshkini; Kolsoum Dinarvand; Zahra Alikhani; Mal Haysom; Mehdi Rasouli (International Journal of Preventive Medicine, 2016)
Background: It is hypothesized that the impacts of life events accumulate and can trigger and promote atherosclerosis in susceptible individuals. In the current study, the correlation of total life stressors during 1 year was investigated relative to coronary artery disease (CAD). Methods: The study population consisted of 148 males and 152 females aged 35-76 years. The subjects were classified as CAD cases and controls according to the results of coronary angiography. The severity of CAD was scored on the basis of the number and the extent of lesions at coronary arteries. The stressful events of life were assessed using Holmes-Rahe Questionnaire and was presented as total psychological stress scores per year (TPSS). Results: The frequency of cigarette smoking, diabetes mellitus, and hypertension was more prevalent in CAD cases than control subjects. The levels of TPSS were increased in patients with CAD compared to the controls (160.3 ± 71.3 vs. 139.8 ± 66.5, P = 0.020). TPSS was also associated positively with the levels of uric acid, erythrocytes counts, erythrocyte sedimentation rate, aspirin consumption, and negatively with high-density lipoprotein-cholesterol and apo-AI. In logistic regression analysis, TPSS correlated with the occurrence of CAD by the odds ratio of 1.773 (1.073-2.930), P = 0.025, but the association was weakened after adjustment for classical risk factors, especially hypertension. TPSS exhibited significant association with the severity of CAD [F (3,274) = 2.6, P = 0.051]. Conclusions: The results suggest that TPSS are associated with the occurrence and severity of CAD significantly, but the association is not independent.